2020
DOI: 10.1186/s12915-019-0708-7
|View full text |Cite
|
Sign up to set email alerts
|

A straightforward approach for bioorthogonal labeling of proteins and organelles in live mammalian cells, using a short peptide tag

Abstract: Background: In the high-resolution microscopy era, genetic code expansion (GCE)-based bioorthogonal labeling offers an elegant way for direct labeling of proteins in live cells with fluorescent dyes. This labeling approach is currently not broadly used in live-cell applications, partly because it needs to be adjusted to the specific protein under study. Results: We present a generic, 14-residue long, N-terminal tag for GCE-based labeling of proteins in live mammalian cells. Using this tag, we generated a libra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…To avoid affecting the levels of expression of endogenous NFL, instead of a site-specific TAG knock-in, we introduced the TAG amber codon at the end of the Nefl gene, in the form of a short linker sequence followed by 3x-FLAG. A similar approach was previously used to develop standardized tags for the click labeling of overexpressed proteins 61 . As illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid affecting the levels of expression of endogenous NFL, instead of a site-specific TAG knock-in, we introduced the TAG amber codon at the end of the Nefl gene, in the form of a short linker sequence followed by 3x-FLAG. A similar approach was previously used to develop standardized tags for the click labeling of overexpressed proteins 61 . As illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[71] Usually, a wide range of various fluorescent dyes is utilizing as fluorescent markers owing to their brightness and full color/emission range. [15,22] While molecular labeling is highly useful for diagnosing and tracking the activities of organelles and biomolecules at a much smaller length scale, [72] the labeling with particulate fluorophores allows the imaging of cells, tissues, and extracellular matrix within biological systems through the interfacial interaction-based approach. [73][74] In this regard, particulate fluorophores such as quantum dots, lanthanide-doped nanoparticles, conjugated polymer nanoparticles, fluorescent silica nanoparticles, etc.…”
Section: A General Labeling Conceptmentioning
confidence: 99%
“…The authors demonstrated selective and efficient labeling of the target proteins that produced superior readings compared to immunolabeling (Beliu et al, 2019). A similar study utilized bicyclo-non-yne lysine (BCN-Lys) (13) to attach a tetrazine dye to the protein of interest via a N-terminal tag in HEK293T and Cos7 cells (Segal et al, 2020). Interestingly, insertion of BCN-Lys in the N-terminal tag was labeled better than BCN insertion within the target protein.…”
Section: Protein Visualization Using Fluorescent Moleculesmentioning
confidence: 99%
“…In addition, the modified tag was found to be compatible in labeling organelle proteins within their acidic environments. Although the authors demonstrated the ability to switch out the HA-tag with other commonly used tags (Myc and FLAG), the results were not as successful, indicating a need for further optimization (Segal et al, 2020). The ease of simply inserting a tag encoding an ncAA led the authors to state the possibility of genomically inserting the modified tag to monitor endogenously expressed proteins.…”
Section: Protein Visualization Using Fluorescent Moleculesmentioning
confidence: 99%